Cortot's Berceuse. (15th September 2015) - Leech‐Wilkinson, Daniel
ABSTRACT Alfred Cortot's 1920 recording of Chopin's Berceuse has some unusual properties – illustrated here in a discussion of the relationships among rubato, loudness, variation form and melody – which shed new light on the score and exemplify the pianist's ability to trigger embodied metaphor with unusual intensity. Comparisons with other recordings are made, and Jeffrey Kallberg's image of the Berceuse as a music box is considered in relation to the layout of the score and Cortot's performance. Drawing on the work of Antonio Cascelli, I compare Schenker's and Cortot's readings of melodic structure, which demonstrate the ecological validity of Cortot's construction. Some of the many respects in which analysis depends upon performance are discussed, as is the likelihood of very different performances in the future and the expectation that analysis will adapt itself to changing approaches to performance. The article is illustrated by Sonic Visualiser analyses presented as YouTube videos.